2020
DOI: 10.1097/01.ogx.0000696612.60869.1b
|View full text |Cite
|
Sign up to set email alerts
|

Elagolix Treatment for Up to 12 Months in Women With Heavy Menstrual Bleeding and Uterine Leiomyomas

Abstract: (Abstracted from Obstet Gynecol 2020;135:1313–1326) Uterine leiomyomas affect up to 80% of reproductive-age women and are the most common benign neoplasm of the uterus. A variety of symptoms occur in approximately half of these women; the most common is heavy menstrual bleeding (HMB), which can result in anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 0 publications
0
37
0
2
Order By: Relevance
“…Of note, in the 12-month study (6-month extension), the authors reported that 87.9% of the women taking elagolix with hormonal add-back therapy met the primary objective. 4 Among the women taking elagolix alone, 89.4% met the primary objective.…”
Section: The Extension Trial Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, in the 12-month study (6-month extension), the authors reported that 87.9% of the women taking elagolix with hormonal add-back therapy met the primary objective. 4 Among the women taking elagolix alone, 89.4% met the primary objective.…”
Section: The Extension Trial Resultsmentioning
confidence: 99%
“…ata from the Elaris UF-1 and UF-2 6-month, phase 3 trials 3 and the results of the Elaris UF-EXTEND trial with a 6-month extension (totaling 12 months of use) 4 were published in 2020, and the 12-month results were discussed in OBG Management (2020;32[7]:35, 39-40). An additional data analysis from the same researchers assessed the effect of elagolix with hormonal add-back therapy in a number of patient subgroups.…”
mentioning
confidence: 99%
“…Further reductions in BMD were observed in long-term extension studies; 66 however, BMD was generally similar to or improved with respect to on-treatment values in patients with posttreatment measurements. 61,62,66,67 In head-to-head comparisons, changes in lumbar spine BMD were similar during 24 weeks of treatment with elagolix 150 mg once daily, elagolix 75 mg twice daily, or DMPA (104 mg/0.65 mL administered on weeks 1 and 12) 61 and greater during 12 weeks of treatment with monthly depot leuprolide acetate 3.75 mg compared with elagolix 150 or 250 mg once daily (Table 3). 68 The difference in BMD reduction with leuprolide was attributed to greater estradiol suppression; on-treatment estradiol concentrations were significantly lower with leuprolide versus elagolix (median, 5 and 32 mg, respectively; p < 0.001).…”
Section: Gnrh Antagonistsmentioning
confidence: 95%
“…Add-back therapy has proved effective for mitigating hypoestrogenic effects associated with GnRH antagonists, including changes in BMD (Table 3). 64,65,67,69 At month 6 in 2 identical, phase 3, randomized, placebo-controlled clinical trials of elagolix in women with heavy menstrual bleeding and uterine fibroids, differences in BMD reduction at most measured sites were statistically significant for elagolix 300 mg twice daily alone compared with placebo ( p < 0.05), whereas changes from baseline in mean BMD in patients receiving elagolix 300 mg twice daily plus add-back therapy (1.0 mg estradiol/0.5 mg norethindrone acetate) were similar to the placebo group. 65 Patients enrolled in these phase 3 trials had the option of continuing treatment with elagolix or elagolix plus add-back therapy in a 6-month extension study.…”
Section: Gnrh Antagonistsmentioning
confidence: 99%
“…Four randomized controlled trials with 1949 participants were included in the study (27)(28)(29)(30). All four trials reported the primary outcome.…”
Section: Included Studiesmentioning
confidence: 99%